Cow/calf profitability: case studies of Kansas cattle producers - Simms, D.D.; Marston, T.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Cost/return analyses of 56 Kansas cow/calf operations were summarized to determine the major factors influencing 1987 and 1988 cow herd profitability. Gross returns and costs on a per cow unit basis were extremely variable. with the bottom 1/3 of these operations essentially breaking even. whereas the high 1/3 profitability group averaged $228.40 per head in net cash returns. Both operating and fixed costs were major determinants of profitability. Reproductive rate (calves weaned per cow exposed) was the major production variable affecting profitability.
Keywords: Beef; Cows; Profitability; Economics; BEEFpro